Chicken gga-miR-103-3p Targets CCNE1 and TFDP2 and Inhibits MDCC-MSB1 Cell Migration. Issue 5 (1st May 2016) - Han, Bo; Lian, Ling; Li, Xin; Zhao, Chunfang; Qu, Lujiang; Liu, Changjun; Song, Jiuzhou; Yang, Ning
Abstract: Marek's disease (MD) is a highly contagious viral neoplastic disease caused by Marek's disease virus (MDV), which can lead to huge economic losses in the poultry industry. Recently, microRNAs (miRNAs) have been found in various cancers and tumors. In recent years, 994 mature miRNAs have been identified through deep sequencing in chickens, but only a few miRNAs have been investigated further in terms of their function. Previously, gga-miR-103-3p was found downregulated in MDV-infected samples by using Solexa deep sequencing. In this study, we further verified the expression of gga-miR-103-3p among MDV-infected spleen, MD lymphoma from liver, noninfected spleen, and noninfected liver, by qPCR. The results showed that the expression of gga-miR-103-3p was decreased in MDV-infected tissues, which was consistent with our previous study. Furthermore, two target genes of gga-miR-103-3p, cyclin E1 ( CCNE1 ) and transcription factor Dp-2 (E2F dimerization partner 2) ( TFDP2 ), were predicted and validated by luciferase reporter assay, qPCR, and western blot analysis. The results suggested that CCNE1 and TFDP2 are direct targets of gga-miR-103-3p in chickens. Subsequent cell proliferation and migration assay showed that gga-miR-103-3p suppressed MDCC-MSB1 migration, but did not obviously modulate MDCC-MSB1 cell proliferation. In conclusion, gga-miR-103-3p targets the CCNE1 and TFDP2 genes, and suppresses cell migration, which indicates that it might play an important role in MD tumor transformation.